PREPARATION AND PHYSICOCHEMICAL CHARACTERISATION OF SWARNA MAKSHIKA BHASMA - Nair, *Raji.R.; Lakshmi, S.Thara (International Journal of Ayurveda and Pharma Research, 2019)
Mineral drugs play an important role in Ayurvedic therapeutics. Makshika, Copper pyrite is considered as Maharasa in Rasasastra. It is described as one among best Rasayanas in classical literatures. This study is an attempt to standardize the process of preparation of Swarna Makshika bhasma. The process commences with selection of raw material, which is the prime and crucial step ahead. Ayurveda Pharmacopoeia of India standards and classical methods were used for the same. Swarna Makshika bhasma was prepared as per the reference from Ayurveda Prakasha (Shodhana) and Rasaratna Samucchayam (Marana). Shodhana (purification) was done by open heating in an iron pan by adding Saindhava (rock salt) and lemon juice. Five Varaha puta with 6000C quantum of heat was opted for Marana. The process was performed using an Electric Muffle furnace. During each step classical methods for analyzing the product (Bhasma) was done which ensured the proper Bhasmeekarana. Swarna Makshika bhasma was then subjected to X-ray Diffraction study which reveals the presence of both haematite (58%) and magnetite (40%) in it and the structural representation of them in Bhasma was also noted. XRF study conducted found that the Bhasma posses 75.54% Iron and rest of the elements within its permissible limits which ultimately unwrap its safety. Scanning Electron Microscope study gave the particle size of Bhasma to be 2microns (50000 X magnification. The particle size recorded can be considered as the desired specification of the final Bhasma.